N-of-1 medicine - Peter Wang; Qiao Ying Leong; Ni Yin Lau; Wei Ying Ng; Siong Peng Kwek; Lester Tan; Shang-Wei Song; Kui You; Li Ming Chong; Isaiah Zhuang; Yoong Hun Ong; Nigel Foo; et al. (Singapore Medical Journal)
The fields of precision and personalised medicine have led to promising advances in tailoring treatment to individual patients. Examples include genome/molecular alteration-guided drug selection, single-patient gene therapy design and synergy-based drug combination development, and these approaches can yield substantially diverse recommendations. Therefore, it is important to define each domain and delineate their commonalities and differences in an effort to develop novel clinical trial designs, streamline workflow development, rethink regulatory considerations, create value in healthcare and economics assessments, and other factors. These and other segments are essential to recognise the diversity within these domains to accelerate their respective workflows towards practice-changing healthcare. To emphasise these points, this article elaborates on the concept of digital health and digital medicine-enabled N-of-1 medicine, which individualises combination regimen and dosing using a patient’s own data. We will conclude with recommendations for consideration when developing novel workflows based on emerging digital-based platforms.